Prospects for including edible insects into the food composition - K. G. Kuznetsova; V. Yu. Sitnov; D. S. Ryabukhin (Пищевые системы)
The use of insects as an alternative protein source is considered a promising strategy for the agricultural development that facilitates solution to the problem of feeding the world’s population. Introduction of insects as a raw material resource into the existing food systems allows enriching products with valuable nutrients and improving their quality characteristics. The review aims at assessment of the world regulatory normative base, analysis of the risks linked with consumption of the new type of foods containing processed insects and determination of promising and profitable directions for sales markets. The paper considers Russian and European technical documentation related to food production and safety, presents traditional methods for processing of entomological biomass to produce semi-finished products from insects, shows specific features of enrichment of certain food products with insect meal and describes changes in the technological parameters improved as a result of these manipulations. Despite the world trend toward inclusion of alternative food resources into human diets, popularity of products from insects in Russia largely depends on public awareness about benefits and taste of such products, public confidence in their safety and support from the government and business. Among advantages of edible insects is their growing in the areas of compact settlement without specific requirements for volumes of land and water resources, as well as their ability to process secondary resources that are not used in human nutrition. However, to realize such an ambitious plan on revision of human food habits, more accurate and reliable studies of control methods and prevention of adulteration of products with insects are necessary.